Qubit compatible superconducting interconnects. (30th November 2017) - Foxen, B; Mutus, J Y; Lucero, E; Graff, R; Megrant, A; Chen, Yu; Quintana, C; Burkett, B; Kelly, J; Jeffrey, E; Yang, Yan; Yu, Anthony; et al.
Abstract: We present a fabrication process for fully superconducting interconnects compatible with superconducting qubit technology. These interconnects allow for the three dimensional integration of quantum circuits without introducing lossy amorphous dielectrics. They are composed of indium bumps several microns tall separated from an aluminum base layer by titanium nitride which serves as a diffusion barrier. We measure the whole structure to be superconducting (transition temperature of 1.1 K), limited by the aluminum. These interconnects have an average critical current of 26.8 mA, and mechanical shear and thermal cycle testing indicate that these devices are mechanically robust. Our process provides a method that reliably yields superconducting interconnects suitable for use with superconducting qubits.